A Journal for Manly Culture: An Exploration of the World’s First Gay Periodical - Stewart, Andrew (Papers of the Bibliographical Society of Canada / Cahiers de la Société bibliographique du Canada)

(untitled) (The Bibliographical Society of Canada/La Société bibliographique du Canada, 2019)
Published by Adolf Brand from 1896 until the rise of Nazism in 1933, Der Eigene was the world’s first homosexual periodical. This article will argue that although many of the ideals espoused in this publication are now considered at best distasteful and at worst inherently wrong and associated with Nazism, there areelements of the publication that are worthy of greater attention in the historiography. I will begin by exploring the publication itself, its ideals and goals, and how it sought to use art to accomplishthem. I will then suggest ways in which Der Eigene challenges our contemporary understanding of homosexuality by tracing clear links from ideas put forth by its contributors to elements of the modernLGBTQ community.